Liquid-liquid phase separation of membrane-less condensates: from biogenesis to function - Guan, Huanyu; Wang, Hui; Cai, Xin; Wang, Jiabo; Chai, Zhixin; Wang, Jikun; Wang, Haibo; Zhang, Ming; Wu, Zhijuan; Zhu, Jiangjiang; Zhong, Jincheng; Yue, Binglin (Frontiers in Cell and Developmental Biology, 2025)
Membrane-less condensates (MLCs) are highly concentrated non-membrane-bounded structures in mammalian cells, comprising heterogeneous mixtures of proteins and/or nucleic acids. As dynamic compartments, MLCs can rapidly exchange components with the cellular environment, and their properties are easily altered in response to environmental signals, thus implicating that they can mediate numerous critical biological functions. A basic understanding of these condensates’ formation, function, and underlying biomolecular driving forces has been obtained in recent years. For example, MLCs form through a liquid-liquid phase separation (LLPS) phenomenon similar to polymer condensation, which is primarily maintained via multivalent interactions of multi-domain proteins or proteins harboring intrinsically disordered regions (IDRs) as well as RNAs with binding sites. Moreover, an accumulating body of research indicates that MLCs are pathophysiologically relevant and involved in gene expression regulation and cellular stress responses. Here, we review the emerging field and explore what is currently known about the varied progress in LLPS of MLCs and how their features affect various cellular process, focusing on RNAs, including in skeletal myogenesis.